A Mixed-Methods Study of Veterans Affairs Providers' Experiences Communicating With Patients About the Affordable Care Act. Issue 5 (1st May 2017) - Martinez, Rachael N.; Gordon, Elisa J.; Tully, Sean; Silva, Abigail; Tarlov, Elizabeth; French, Dustin D.; Huo, Zhiping; Smith, Bridget M.; Gordon, Howard S.; Stroupe, Kevin T.
ABSTRACT: Objective: The provisions under the Affordable Care Act (ACA) can potentially increase insurance options for Veterans. Veterans must be informed about their options, and potential benefits and challenges associated with use of multiple health care systems. This study aimed to assess VA providers' perceptions of how they contributed to Veterans' health care decision-making within the health care context established by the ACA. Materials and Methods: A mixed-methods approach including an online survey and semi-structured interviews was used to assess the experiences of health care providers (e.g., physicians, nurses, and social workers) communicating with Veterans about the ACA. Closed-ended survey questions were analyzed using descriptive statistics. Qualitative analysis of open-ended responses to the survey and semi-structured interview entailed thematic analysis, which involved identifying themes and patterns within and across participants until reaching saturation. Results: A total of 251 providers completed the survey (20% response rate), and 26 providers completed a semi-structured interview (23% participation rate). Most providers (75.3%) reported being only "a little" or "somewhat" knowledgeable about the overall provisions of the ACA, and 90.8% of providers reported needing more information about the ACA. Key themes that emerged from the qualitative analyses included a variety of issues related to the ACA. According to providers, Veterans raised concerns about: signing up for the ACA, retaining VA benefits, knowledge about VA benefits and the ACA, understanding implications of insurance coverage through the ACA, and affordability of the ACA. Providers expressed the need for provider and patient educational resources. Conclusion: Our findings suggest that Veterans and their providers encounter challenges comprehending recent policy changes and navigating ongoing dual health care use. According to providers, Veterans' knowledge about the ACA can affect their ability to make informed health care decisions. Equipping patients and providers with more information about the ACA, and promoting communication between patients and providers may foster shared decision-making processes with regard to health care and treatment options. Strategies to improve knowledge transfer and patient-provider communication about policy changes warrant further investigation.